Application of Pedagogical Content Knowledge (PCK) on Magnetic Materials Assisted by Flash Player Media to Improve Student Learning Outcomes and Activeness - Gelu, Afrianus; Ellianawati, Ellianawati (Physics Communication, 2024)
Pedagogical Content Knowledge (PCK) is the interaction between pedagogy and content. PCK describes the ability of teachers to integrate knowledge of the content into their knowledge of learning and student characteristics that can guide the learning situation. Flash Player media is software used to stream and view video, audio, and multimedia on a computer or supported mobile device. The purpose of this research is to know the application of PCK strategy based on flash player media to increase the mastery of concept and student learning activity. The research method used is classroom action research. Data collection techniques are carried out through tests, observations and interviews during learning. From the research results obtained t count 16,087 t table 2,02 showing that the PCK strategy based on flash player media can improve the mastery of student concepts. The observation data in the experimental class shows that there is an increase in student learning activity. In general, the conclusion that can be drawn from this research is PCK strategy based on flash player media has positive effect in the case of the improvement of learning outcomes and student learning activeness